Molecular docking and molecular dynamics simulations discover curcumin analogs as potential wound healing agents - Govindaraj Sabarees; Vadivel Velmurugan; Viswas Raja Solomon (Chemical Physics Impact, 2024)
Chronic non-healing wounds impose a significant economic burden on the healthcare system. Among the existing strategies in wound healing therapy, targeting specific enzymes, namely tyrosyl-tRNA synthetase, TGFBR1, IL-1β, and Pseudomonas aeruginosa MvfR, represents an important aspect of the strategy of wound healing. Our research focuses on creating new curcumin hybrids (SV01-SV20) for harnessing wound healing activities and possesses considerable therapeutic implications. The compounds were designed and evaluated through in-silico screening using Molinspiration Cheminformatics, Osiris Property Explorer, AdmetSAR, and SwissADME. The initial filtering process identified the top 19 hybrids, which were then subjected to docking using the AutoDock tool. The results of the molecular docking analysis indicate that the curcumin hybrids, specifically tyrosyl-tRNA synthetase (SV09, SV15), TGFBR1 (SV01, and SV11), IL-1β (SV07, SV08), and Pseudomonas aeruginosa MvfR (SV09, SV13), showed the most significant binding energies (-8.69, -9.01, -8.49, -8.13, -8.48, -6.14, -9.7, and -9.2 kcal/mol, respectively) among the designed compounds. The binding energies were higher than the standard curcumin, indicating a potentially more substantial interaction with the target. Extensive molecular dynamics simulations confirmed the stability of these derivatives throughout the 100 ns simulation; the ligand-protein complexes maintained structural stability. The designed compounds demonstrated favorable pharmacokinetic properties, drug-likeness scores, bioactivity assessments, adherence to Lipinski's rule of five, and low toxicity risks. Overall, results consistently demonstrated that SV01, SV07, SV08, SV09, SV11, SV13, and SV15 compounds hold significant potential as effective agents in treating chronic wounds.